Assisted suicide for prisoners? Stakeholder and prisoner perspectives. Issue 8 (13th September 2016) - Shaw, David M.; Elger, Bernice S.
ABSTRACT: For a wider project on aging in prison, the authors interviewed 35 older prisoners and 24 stakeholders (prison staff, prison healthcare professionals, and policy makers) about healthcare for prisoners. In all, 6 prisoners and 3 stakeholders spontaneously expressed their attitudes concerning assisted suicide. Some prisoners seek assisted suicide for medical reasons and others because they regard spending the rest of their lives in prison as undignified. However, stakeholders identified several ethical and practical challenges in providing assisted suicide to prisoners. This article presents these perspectives on assisted suicide in prison and provides an ethical analysis of the issues raised.